Quantum phase transitions - Sachdev, Subir (Cambridge University Press, 1999)
Quantum Phase Transitions details the fundamental changes that can occur in the macroscopic nature of matter at zero temperature due to small variations in a given external parameter. The author develops the theory of quantum phase transitions in the simplest possible class of nondisordered, interacting systems--the quantum Ising and rotor models. He pays particular attention to their non-zero temperature dynamic and transport properties in the vicinity of the quantum critical point. Throughout, experimental results are interwoven with theoretical models, and well over 500 references are included.